2017
DOI: 10.1093/ntr/ntx126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensive Personalized “5As+5Rs” Intervention on Smoking Cessation in Hospitalized Acute Coronary Syndrome Patients Not Ready to Quit Immediately: A Randomized Controlled Trial

Abstract: Smoking has a major impact on acute stages of ACS for recurrent ischemic events and long-term outcomes. However, there are few evidence-based treatments for smokers who are not ready to quit. This study described a cessation intervention initiated during hospitalization and included 15 intensive follow-up aimed at enabling ACS smokers who were not ready to quit immediately to deliver adequate motivational and behavior change counseling. Given its effectiveness demonstrated in this prospective study, this inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
8
0
4
Order By: Relevance
“…The studies included a total of 13 141 participants from 11 countries. Seven studies (29%) were carried out in China [27,29,35,36,38,44,45], three (13%) each in India [39,42,46], Brazil [30,32,40] and Iran [22,26,33], two (8%) each in Malaysia [28,31] and South Africa [24,37] and one (4%) each in Pakistan [41], Syria [43], Thailand [23] and Turkey [34]. Four studies recruited participants from the community, one from a prison, and the remaining 19 recruited participants from medical clinics.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies included a total of 13 141 participants from 11 countries. Seven studies (29%) were carried out in China [27,29,35,36,38,44,45], three (13%) each in India [39,42,46], Brazil [30,32,40] and Iran [22,26,33], two (8%) each in Malaysia [28,31] and South Africa [24,37] and one (4%) each in Pakistan [41], Syria [43], Thailand [23] and Turkey [34]. Four studies recruited participants from the community, one from a prison, and the remaining 19 recruited participants from medical clinics.…”
Section: Resultsmentioning
confidence: 99%
“…A smaller number of studies (eight of 25; 32%) reported the method employed for allocation sequence concealment prior to participant enrollment, such as using sequentially numbered opaque envelopes [30,35,37,43,44], pulling numbers out of a box [45] or blinded treatment providers [38,40]. A smaller number of studies (eight of 25; 32%) reported the method employed for allocation sequence concealment prior to participant enrollment, such as using sequentially numbered opaque envelopes [30,35,37,43,44], pulling numbers out of a box [45] or blinded treatment providers [38,40].…”
Section: Selection Biasmentioning
confidence: 99%
See 3 more Smart Citations